THE MONETARY POLICY OF CENTRAL AND EAST EUROPEAN COUNTRIES DURING THE CORONAVIRUS CRISIS - Monica Ionelia MARGARIT (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice)
The current pandemic crisis is a unique challenge, with several economic and social consequences experienced by the entire world. In order to prevent the spread of the coronavirus, the affected states have established a series of social distancing measures and even quarantine measures. They had huge implications on the global economy. This paper focuses on the main monetary policy decisions taken by Central and East European banks in the current pandemic crisis. The response of economic policies to this crisis were remarkable. The CEE countries have implemented measures which aimed at four main objectives: honoring, first and foremost, the urgent needs of the health sector, supporting economic activity and employment, maintaining monetary and financial stability and paving the way for future recovery. We believe that central banks have responded quickly in the current crisis, in many cases, the decision being made long before the official measures have clarified the scale and seriousness of the crises.